A comparative study on phytochemicals and antioxidant activity of different parts of pumpkin (Cucurbita maxima) - Sanjukta Kar; Suchandra Dutta; Rubina Yasmin (Food Chemistry Advances, 2023)
Fruit and vegetable waste is a rich source of bioactive compounds that can be extracted or transformed into high-value products. In some parts of India, pumpkin leaves and flowers are rarely eaten as food. But despite being a rich source of bioactive chemicals with nutritional benefits, pumpkin seeds, and skins are frequently regarded as waste. The study involves the quantitative estimation of the antioxidant activity and phytochemicals content of the various parts of aqueous and isopropanol extracts of Cucurbita maxima plant. Pumpkin leaf exhibits the maximum moisture content (85.76 %), followed by pumpkin flower (79.42 %), pumpkin peel (71.44 %), and pumpkin seeds (3.23 %). The TPC and TFC of the isopropanol extract of pumpkin seed have been found the highest;41.05 mg GAE/g and 829.86 mg QE/g respectively. The highest% inhibition of DPPH radical scavenging activity was found in the isopropanol extract of pumpkin peel; 90.35 % and the lowest was found in the aqueous extract of pumpkin seeds 48.41 %. The aqueous extract of pumpkin peel has the highest value with a TAC of 123.33 mg AAE/g. The finding of the current study mainly highlights the importance of underutilized parts of pumpkin rather than discarding them as waste.